ANALISIS KINERJA USAHA MIKRO KECIL (Studi Kasus Pada PT. PNM Mekaar Syariah Takengon Kabupaten Aceh Tengah) - Yani Ristika; Sri Yanna (Ekonomika : Jurnal Ekonomi dan Pembangunan, 2023)
The aim of the research is to analyze the performance of Micro, Small and Medium Enterprises through analysis of 1) The influence of credit on the income of MSEs and customers, 2) The effect of loan duration on the income of MSMEs and customers, 3) The influence of the Business Capacity Development (PKU) program on the income of actors and customers. Study on PT. National Capital Madani Mekaar Syariah Takengon. Research results on a sample of 70 customers engaged in culinary businesses, farming and livestock businesses as well as other service businesses. Based on statistical data processing and testing, there is a positive influence from the aspect of utilizing the Business Capacity Development (PKU) program provided by the company on the income of micro and small businesses. The loan length factor has a negative effect, but the credit size does not have a significant effect. But simultaneously all credit factors, length of loan and PKU) influence income, with a contribution of 21%.